PENGARUH PROFESIONALISME DAN PERILAKU DISFUNGSIONAL AUDITOR PADA KUALITAS AUDIT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Baiq Armiana Malahayati; Maslichah Maslichah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACT This research was conducted to analyze the Effect of Professionalism and Auditor's Dysfunctional Behavior on Audit Quality with Job Satisfaction as a Moderating Variable